THE IMPACT OF COLLABORATIVE GOVERNANCE ON MSMES RECOVERY IN DKI JAKARTA DURING THE COVID-19 PANDEMIC - Nana Nurwaesari; Fajar Bambang Hirawan; Safendrri Komara Ragamustari (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
In the recovery of MSMEs during the pandemic, the government cannot do it alone. Therefore, collaboration from various parties is needed. This study aims to analyze the impact of Collaborative Governance in the recovery of Micro, Small, and Medium Enterprises (MSMEs) in Jakarta during the COVID-19 pandemic by evaluating the Large-Scale Social Collaboration (LSSC) of MSMEs from June 2020 to June 2021. In addition, to analyze the extent to which Collaborative Governance is implemented in the LSSC of MSMEs program, the researcher used five important indicators based on Collaborative Governance theory. By using qualitative methods, the data obtained through in-depth interviews with several stakeholders involved and MSME owners as recipients of the program assistance. Data analysis was carried out using thematic analysis to obtain indicators that describe the program effectiveness from the implementers and indicators of the satisfaction of MSME actors with the assistance received through this program. Then, all these indicators are re-analyzed using the SWOT framework. The study found that Collaborative Governance has been running quite well, but stakeholders have not really involved MSME Activists in the Large-Scale Social Collaboration program as one of the steps in restoring MSMEs in Jakarta. In this finding, the researcher recommends several solutions such as, more massive publication and socialization is needed to invite more collaborators, the governance and mechanism of the LSSC of MSMEs program needs to be improved, as well as revitalizing the program. Therefore, the government also needs to implement some steps to maintain the sustainability of this program.